THE STRENGTHEN STRATEGY OF MUSLIM MODERATE CHARACTERS IN EARLY CHILDREN AGE BASED ON LEARNING CENTER - Mardiyah, Asih Andriyati; Rozi, Syaikhu (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2019)
This article was written based on the results of qualitative research to describe the character of moderate Muslim children who were strengthened at TK Islam Terpadu Permata Mulia Mojokerto and its strategies. The data was obtained from observations, interviews, and studies of curriculum documents, report cards, etc. The data were analyzed by using the path developed of Miles and Huberman. The conclusions of the research were: 1) There are five strengthen character of muslim moderatein this school, they are independence, love the Quran, honest, brave, and leadership. 2) The strengthen Character strategy was obtained by learning in the classroom and outside the class. There are four models that were used to strengthen the character of muslim moderate, they were a model of preparatory activities, classroom learning, preparation centers, role playing, blocks, and natural centers; and outing.